Evidence for cognitive plasticity during pregnancy via enhanced learning and memory. Issue 5 (28th May 2022) - Callaghan, Bridget; McCormack, Clare; Tottenham, Nim; Monk, Catherine
ABSTRACT: Human and animal neuroscience studies support the view that plastic shifts occur in the brain during pregnancy that support the emergence of new maternal behaviours. The idea of adaptive plasticity in pregnancy is at odds with the notion of "baby brain", in which pregnant women describe the onset of forgetfulness. While inconsistent evidence for memory deficits during pregnancy has been reported, few studies have investigated spatial associative memory (which is consistently enhanced in studies of pregnant rodents). Moreover, most studies assess domain-general stimuli, which might miss adaptations specific to parent-relevant stimuli. In the present study, we examined the retention of spatial associative memory for parenting-relevant and non-parenting-relevant stimuli across 4-weeks in a sample of women in their third trimester of pregnancy, and compared their performance to a sample of never pregnant women. We demonstrated that relative to never pregnant women, pregnant women exhibited enhanced long-term retention of object-scene-location associations (spatial associative memory), as well as better initial learning about parenting-relevant, relative to non-parenting-relevant, stimuli. Thus, similar to studies in rodents, cognitive improvements were seen during pregnancy in humans, and those improvements were specific to the domain of spatial associative retention, and in the recognition of stimuli relevant to parenting.